Penerapan Kebijakan Tentang Prinsip Kehati-Hatian Dalam Pemberian Kredit Perbankan - Nanang Tri Budiman; Supianto Supianto (Universitas Widya Gama Malang, 2020)
A bank is an effort to collect funds from the public in the form of savings and distribute them back to the community in the form of credit or other forms in order to improve people's lives. In distributing credit to the public, each bank is required to implement the precautionary principle in channeling loans. This study aims to determine the application of the precautionary principle applied in the process of providing bank credit. This study uses a normative juridical research method with a statute approach and a conceptual approach. Based on the results of the study, it was found that the application of the precautionary principle was carried out in the form of obligation to formulate and implement bank credit policies for commercial banks, maximum credit limits, assessment of asset quality, debtor information systems, the principle of knowing customers and the existence of guarantees in providing credit.